PENGEMBANGAN ALAT PERAGA DIORAMA BERBASIS AUGMENTED REALITY PADA PEMBELAJARAN IPAS: MEMAHAMI SISTEM PERNAPASAN MANUSIA DAN MEKANISMENYA DI KELAS V SEKOLAH DASAR - Andre Pratama Sitepu; Syahrial; Alirmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop Augmented Reality (AR)-based teaching aids for learning the human respiratory system in fifth grade elementary schools in the Natural and Social Sciences (IPAS) subject. These teaching aids are designed to improve students' understanding of abstract concepts through interactive and visual learning experiences. This study also aims to assess the practicality of the teaching aids, content validity, and their impact on student engagement and motivation. Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, these teaching aids were tested on students to evaluate their effectiveness in improving students' understanding of the material being taught.